2019
DOI: 10.33545/gynae.2019.v3.i6e.429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of efficacy of micronized progesterone by vaginal route for prevention of preterm labour

Abstract: Preterm birth is a major health problem for neonates, family, country, and society in general. In our study 106 singleton pregnancies with no high risks were included to study the efficacy and safety of natural micronized progesterone in prevention of preterm labour. Aim: To assess efficacy of natural micronized progesterone by vaginal route in prevention of preterm labour. Material and Methods: It was a prospective study conducted at our tertiary care centre Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results obtained show than the use of progeterones both orally and vaginally, are comparable to parity. This is similar to the studies of Mostafa AH [11] and Deshpande H et al [12] . Mostafa AH 11 study found mean age for oral group was (28.7±7.2) and for the vaginal group was (28.1±8) which showed insignificant difference statistically.…”
Section: Comparison Of Birth Weight Of Neonates Between Groupssupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained show than the use of progeterones both orally and vaginally, are comparable to parity. This is similar to the studies of Mostafa AH [11] and Deshpande H et al [12] . Mostafa AH 11 study found mean age for oral group was (28.7±7.2) and for the vaginal group was (28.1±8) which showed insignificant difference statistically.…”
Section: Comparison Of Birth Weight Of Neonates Between Groupssupporting
confidence: 92%
“…Mostafa AH 11 study found mean age for oral group was (28.7±7.2) and for the vaginal group was (28.1±8) which showed insignificant difference statistically. Deshpande H et al [12] prospective study assessing efficacy of natural micronized progesterone by vaginal route in prevention of PTL found maternal age was 28±4.3 in progesterone group versus 28.2±4.5 in placebo group. The mean gestational age of patients in OMP group and VMP group was 31.37 ± 1.94 weeks and 33.49 ± 2.49 weeks respectively.…”
Section: Comparison Of Birth Weight Of Neonates Between Groupsmentioning
confidence: 99%
“…5 When administered through vagina, however, it avoids the first-pass effect by the liver, is absorbed quickly, has increased bioavailability, directly affects the uterus, and is maintained in a high concentration in the serum. 6 Vaginal progesterone gel is administered through a specific applicator and a dose of 90 mg was used in all published studies. Vaginal progesterone suppository is inserted in the vagina with clean hands or plastic gloves.…”
Section: Introductionmentioning
confidence: 99%